MICROPROPAGATION OF POTATO (Solanum tuberosum L.) cv. GRANOLA IN LIQUID MEDIUM USING AERATION SYSTEM FOR G0 SEED PRODUCTION - Karyanti Karyanti; Hayat Khairiyah; Tati Sukarnih; Yayan Rudiyana; Isni Nasrifah; Aida Wulansari; Shinta Magdalena Septiani; Dasumiati Dasumiati (Balai Bioteknologi, Badan Pengkajian dan Penerapan Teknologi (BPPT), 2022)
ABSTRACT Disease-free potato seeds of high quality can be obtained via in vitro culture. The use of liquid medium during in vitro cultures might boost the number of plantlets produced, however, the problem of hyperhydricity in plantlets was often encountered. This study aimed to investigate effects of different sucrose concentrations and application of aeration system on micropropagation of potato cv. Granola using liquid medium. Aseptic nodal explants with 3-4 nodes from established in vitro cultures were subjected to MS liquid medium with a factorial treatment of three sucrose concentrations (0, 7.5, 15 g. L-1) and two culture (with and without aeration). The results showed that MS medium with 7.5 g L-1 sucrose was the best medium to produce the highest number of shoots and nodes. Furthermore, it was found that application of aeration system in MS liquid culture decreased plantlet hyperhydricity and increased the number of shoots, number nodes, plantlet height, as well as improved plantlet morphology and vigor. Application of the aeration system in liquid medium produced 200-230 new potato plants per bioreactor in the acclimatization stage and an average of 2773.5 G0 mini tubers. ABSTRAK Benih kentang bebas penyakit berkualitas tinggi dapat diperoleh dari kultur in vitro. Penggunaan media cair selama kultur in vitro dapat meningkatkan jumlah planlet yang dihasilkan, namun masalah hiperhidrisitas plantlet masih sering dijumpai. Penelitian ini bertujuan mengetahui pengaruh perbedaan konsentrasi sukrosa dan penerapan sistem aerasi terhadap perbanyakan kentang cv. Granola menggunakan media cair. Eksplan dengan 3-4 nodus dari kultur in vitro ditumbuhkan pada media cair MS dengan perlakuan faktorial, faktor pertama: tiga tingkat konsentrasi sukrosa (0, 7,5, 15 g. L-1) dan faktor kedua: dua sistem kultur (dengan dan tanpa aplikasi aerasi). Hasil menunjukkan bahwa media MS dengan 7,5 g. L-1 sukrosa merupakan media terbaik untuk menghasilkan jumlah tunas dan nodus terbanyak. Selanjutnya ditemukan bahwa penerapan sistem aerasi pada kultur cair MS menurunkan hiperhidrisitas plantlet dan meningkatkan jumlah tunas, jumlah buku, tinggi plantlet, serta memperbaiki morfologi dan vigor plantlet. Penerapan sistem aerasi pada media cair menghasilkan 200-230 tanaman kentang baru per bioreaktor dalam tahap aklimatisasi dan rata-rata 2773,5 G0 umbi mini.